Internalisasi Nilai-Nilai Religius Pada Pendidikan Melalui Kebijakan Full day School - Sugesti Riza Nor Aida (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract: Education can involve conscious and systematic efforts to create an environment and teaching and learning activities so that students are active in expanding their potential, religious spiritual strength, but with the rise of juvenile delinquency caused by the lack of internalization of religious values ​​in students, so the full day school policy was born. in Indonesia in order to improve the religious values ​​of students. This study aims to find out and examine more deeply about the internalization of religious values ​​in students through the full day school program implemented by educational institutions. This research method uses a type of library research (library) with a descriptive analysis approach to describe the real situation that is currently happening, then the data collected will be processed according to existing procedures. This study shows the results that full day school education is carried out in schools that help educate, nurture and teach all students, especially in student morale. The introduction of full day school education will enable the teaching of Islamic values ​​in an integrated manner to all students. Keywords: Internalization of Religious Values, Education, Full Day School